CSR @ Nilai: Kembara Ilmu JSKM / Nor Ashikin Sahrom and Siti Noor Dina Ahmad - Sahrom, Nor Ashikin; Ahmad, Siti Noor Dina (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Kembara Ilmu JSKM was organized by the College of Computing, Informatics and Media Studies UiTM Negeri Sembilan Kampus Kuala Pilah on September 10 2022. A total of 30 students aged between 10 to 12 years old from Semarak Flat, Nilai. The program was held at Semarak Resource Centre, Nilai, in front of the residence area. The session was conducted by all lecturers from mathematics and computer science backgrounds. In this program, the students are given the introduction of STEM and fun games such as Mathematic is Fun-FLIP CARD and Mathematic is Fun-BINGO. The manager of Semarak Resource Centre, Puan Muzaliza Musa and the founder, Puan Asfalaila Abu Bakar, were very helpful and supportive. Positive feedback was also given by the student involved throughout the program. The figures below show all the activities involved during the program.